2019
DOI: 10.1109/access.2019.2946401
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Leading Causes of Traffic Fatalities Using XGBoost and Grid-Based Analysis: A City Management Perspective

Abstract: Traffic accidents have been one of the most important global public problems. It has caused a severe loss of human lives and property every year. Studying the influential factors of accidents can help find the reasons behind. This can facilitate the design of effective measures and policies to reduce the traffic fatality rate and improve road safety. However, most of the existing research either adopted methods based on linear assumption or neglected to further evaluate the spatial relationships. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 52 publications
0
35
0
1
Order By: Relevance
“…These features have been partly discussed by previous literature [4], [10], [22], [46]. All of them exhibit explicit threats that lead to fatal accidents.…”
Section: Discussion and Spatial Relationshipsmentioning
confidence: 91%
See 1 more Smart Citation
“…These features have been partly discussed by previous literature [4], [10], [22], [46]. All of them exhibit explicit threats that lead to fatal accidents.…”
Section: Discussion and Spatial Relationshipsmentioning
confidence: 91%
“…For example, VSAFETY2_W and VTYPE_3 are talking about two typical Vulnerable Road Users (VRUs), which are motorcycle drivers and pedestrians. Studies have shown that these VRUs have five times higher fatality rates than typical car-car accidents [46] because they have no protection equipment such as seat belts or airbags.…”
Section: Discussion and Spatial Relationshipsmentioning
confidence: 99%
“…From studies in other fields, the XGBoost model performs well in predicting nonlinear time series [26][27][28][29]. By integrating multiple CART trees, the XGBoost model can acquire a better generalization performance than single one.…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning, also known as deep structured learning or hierarchical learning, is a class of machine learning that uses multiple layers of non-linear processing units for feature selection and data modeling [20]. Due to its powerful learning ability, deep learning has been applied to a number of fields such as computer vision, speech recognition, language processing [21,22], and has achieved state-of-the-art performance [23].Development of deep learning can be traced back to the machine learning technology. Due to the intrinsic linear assumption of traditional statistical methods, scholars tried to adopt non-linear machine learning methods to better fit the non-linear mechanism of real-world data like air pollution.…”
mentioning
confidence: 99%
“…Deep learning, also known as deep structured learning or hierarchical learning, is a class of machine learning that uses multiple layers of non-linear processing units for feature selection and data modeling [20]. Due to its powerful learning ability, deep learning has been applied to a number of fields such as computer vision, speech recognition, language processing [21,22], and has achieved state-of-the-art performance [23].…”
mentioning
confidence: 99%